Engineering (Bio)Materials through Shrinkage and Expansion. Issue 14 (16th June 2021) - Wang, Mian; Li, Wanlu; Tang, Guosheng; Garciamendez‐Mijares, Carlos Ezio; Zhang, Yu Shrike
Abstract: Although various (bio)fabrication technologies have achieved revolutionary progress in the past decades, engineered constructs still fall short of expectations owing to their inability to attain precisely designable functions. Shrinkable and expandable (bio)materials feature unique characteristics leading to size‐/shape‐shifting and thus have exhibited a strong potential to equip current engineering technologies with promoted capacities toward applications in biomedicine. In this progress report, the advances of size‐/shape‐shifting (bio)materials enabled by various stimuli, are evaluated; furthermore, representative biomedical applications associated with size‐/shape‐shifting (bio)materials are also exemplified. Toward the future, the combination of size‐/shape‐shifting (bio)materials and 3D/4D fabrication technologies presents a wide range of possibilities for further development of intricate functional architectures. Abstract : This progress report systematically summarizes representative size‐/shape‐shifting mechanisms used toward engineering (bio)materials. With such a unique maneuverability, numerous biomedical applications have been made possible in the fields of tissue engineering, imaging, drug delivery, 4D printing, medical devices, and nanofabrication.